Optimal progressivity of personal income tax: A general equilibrium evaluation for Spain - Darío Serrano-Puente (SERIEs - Journal of the Spanish Economic Association, 2020)
Is the Spanish economy positioned at its optimal progressivity level in personal income tax? This article quantifies the aggregate, distributional, and welfare consequences of moving toward such an optimal level. A heterogeneous households general equilibrium model featuring both life cycle and dynastic elements is calibrated to replicate some characteristics of the Spanish economy and used to evaluate potential reforms of the tax system. The findings suggest that increasing progressivity would be optimal, even though it would involve an efficiency loss. The optimal reform of the tax schedule would reduce wealth and income inequality at the cost of negative effects on capital, labor, and output. Finally, these theoretical results are evaluated using tax microdata and describe a current scenario where the income-top households typically face suboptimal effective average tax rates.
Keywords: D31; C68; E62; H21; 330; Income tax; Progressivity; Inequality; Income and wealth distribution; General equilibrium; Heterogeneous agents